EVALUASI DAMPAK INFLASI, NILAI TUKAR, DAN SUKU BUNGA TERHADAP IHSG DI BURSA EFEK INDONESIA - Fransisca Maharani; Zabrina Destrya Fadila; Ayu Nurafni Octavia (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2025)
The company's prospects can be one of the things given by a company to promise in the future, this will encourage investors to invest their shares in the hope of regular dividend distribution from the company. This research was conducted with the aim of analyzing and proving whether or not there is an influence of inflation, interest rates, and the rupiah exchange rate on the Composite Stock Price Index (IHSG). The type of data source was obtained from the financial statements of companies listed on the Indonesia Stock Exchange in the period 2019-2023. Purposive sampling and documentation were used as data collection techniques. The results of the t-test showed that the inflation variable partially affected the Composite Stock Price Index (IHSG), while the interest rate and rupiah exchange rate variables partially did not affect the Composite Stock Price Index (IHSG). And the results of the f-test showed that together Inflation, Interest Rates, and the Rupiah Exchange Rate had a significant influence on the Composite Stock Price Index (IHSG).